Interaction of OsRopGEF3 Protein With OsRac3 to Regulate Root Hair Elongation and Reactive Oxygen Species Formation in Rice (Oryza sativa) - Kim, Eui-Jung; Hong, Woo-Jong; Tun, Win; An, Gynheung; Kim, Sun-Tae; Kim, Yu-Jin; Jung, Ki-Hong (Frontiers in Plant Science, 2021)
Root hairs are tip-growing cells that emerge from the root epidermis and play a role in water and nutrient uptake. One of the key signaling steps for polar cell elongation is the formation of Rho-GTP by accelerating the intrinsic exchange activity of the Rho-of-plant (ROP) or the Rac GTPase protein; this step is activated through the interaction with the plant Rho guanine nucleotide exchange factor (RopGEFs). The molecular players involved in root hair growth in rice are largely unknown. Here we performed the functional analysis of OsRopGEF3, which is highly expressed in the root hair tissues among the OsRopGEF family genes in rice. To reveal the role of OsRopGEF3, we analyzed the phenotype of loss-of-function mutants of OsRopGEF3, which were generated using the CRISPR-Cas9 system. The mutants had reduced root hair length and increased root hair width. In addition, we confirmed that reactive oxygen species (ROS) were highly reduced in the root hairs of the osropgef3 mutant. The pairwise yeast two-hybrid experiments between OsRopGEF3 and OsROP/Rac proteins in rice revealed that the OsRopGEF3 protein interacts with OsRac3. This interaction and co-localization at the same subcellular organelles were again verified in tobacco leaf cells and rice root protoplasts via bimolecular functional complementation (BiFC) assay. Furthermore, among the three respiratory burst oxidase homolog (OsRBOH) genes that are highly expressed in rice root hair cells, we found that OsRBOH5 can interact with OsRac3. Our results demonstrate an interaction network model wherein OsRopGEF3 converts the GDP of OsRac3 into GTP, and OsRac3-GTP then interacts with the N-terminal of OsRBOH5 to produce ROS, thereby suggesting OsRopGEF3 as a key regulating factor in rice root hair growth.